SEPTIC COMPLICATIONS AFTER THE USE OF GLUCOCORTICOIDS (RESULTS OF CLINICAL LABORATORY AND PATHOMORPHOLOGICAL STUDIES) - Hrytsai, Mykola; Hryhorovskyi, Valerii; Tsokalo, Vasyl; Sabadosh, Vasyl; Kuzub, Taisiia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
In numerous articles, monographs, and textbooks, the aspects of local application of glucocorticoid injections at the current stage of development of rheumatology are considered from the point of view of expediency, effectiveness, and safety. Factors affecting the effectiveness of this method are analyzed. Periarticular and/or intra-articular injections of corticosteroids are included in various recommendations and protocols for the treatment of arthrosis and rheumatic joint lesions available today. Objective. Determination of pathomorphological, clinical and laboratory manifestations of the infectious process after local administration of glucocorticoid drugs. Methods. Clinical, anamnestic, laboratory, bacteriological and pathomorphological data of 34 patients with infectious complications were analyzed. Results. The administration of long-acting drugs was most often used: DIPROSPAN — 13 (38.2 %) cases; KENALOG — 5 (14.7 %); DEPOS — 3 (8.8 %); FLOSTERON — 2 (5.9 %); a short-acting drug (methylprednisolone acetate (METYPRED), hydrocortisone acetate) was used in 11 (32.4 %) cases. At the time of hospitalization in the clinic, the infectious process was in 8 (23.5 %) patients in the acute stage, 10 (29.4 %) in the subacute stage, and in another 16 (47.1 %) in the chronic stage, 13 (38.2 %) of which are in the active fistula phase. Conclusions. Pathomorphological manifestations and signs of a purulent-necrotic and purulent-inflammatory infectious process (infectious complications) after local administration of glucocorticoid drugs accompany and are closely statistically significantly interrelated with typical clinical and laboratory manifestations (leukocytosis with a «shift of the leukocyte formula to the left», an increase in ESR and level CRP) and etiology («bacteriology») of the infectious process.